2019
DOI: 10.1371/journal.pone.0223919
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial nitric oxide synthase limits host immunity to control disseminated Candida albicans infections in mice

Abstract: Three isoforms of nitric oxide synthase (NOS) occur in mammals. High levels of NO produced by NOS2/iNOS can protect against bacterial and parasitic infections, but the role of NOS in fungal innate immunity is less clear. Compared to wild type mice, Nos3-/- mice showed significantly higher survival of candidemia caused by Candida albicans SC5314. NOS3/eNOS is expressed by endothelial cells in the kidney, and colonization of this organ was decreased during the sub-acute stage of disseminated candidiasis. Nos3-/-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 57 publications
(79 reference statements)
1
7
0
Order By: Relevance
“…Our data showed that kidney is the primary target organ where C. albicans persists, and this is consistent with previous reports that indicate the importance of renal immunity in experimental disseminated candidiasis and subsequent mouse mortality ( Spellberg et al, 2003 ; MacCallum & Odds, 2005 ; Lionakis et al, 2011 ; Navarathna et al, 2012 , 2019 ; Hebecker et al, 2016 ). In particular, despite the ablation of TRMs in all peripheral organs in CD169-DTR mice, kidneys remained as the only organ with persisting C. albicans , hence highlighting the distinctive role of kidney TRMs in systemic Candida immunity.…”
Section: Discussionsupporting
confidence: 93%
“…Our data showed that kidney is the primary target organ where C. albicans persists, and this is consistent with previous reports that indicate the importance of renal immunity in experimental disseminated candidiasis and subsequent mouse mortality ( Spellberg et al, 2003 ; MacCallum & Odds, 2005 ; Lionakis et al, 2011 ; Navarathna et al, 2012 , 2019 ; Hebecker et al, 2016 ). In particular, despite the ablation of TRMs in all peripheral organs in CD169-DTR mice, kidneys remained as the only organ with persisting C. albicans , hence highlighting the distinctive role of kidney TRMs in systemic Candida immunity.…”
Section: Discussionsupporting
confidence: 93%
“…(Brown, 2011), supporting our conclusion that neutrophil suppression is an important strategy of C. albicans during infection that, if rescued, could represent an exciting therapeutic opportunity. RNS has well characterised, highly candidacidal effects (Rementería, García-Tobalina and Sevilla, 1995; Vazquez-Torres et al ., 1995; Tillmann, Gow and Brown, 2011; Navarathna, Lionakis and Roberts, 2019). Similarly, Macherla et al .…”
Section: Discussionmentioning
confidence: 99%
“…Following recruitment, neutrophils have multiple mechanisms of eliminating C. albicans , including the production of reactive oxygen (ROS) and nitrogen (RNS) species (Winterbourn et al ., 2006). Inhibition of inducible nitric oxide synthase (iNOS) leads to increased mortality in mouse models of C. albicans infections, showing the importance of RNS mediated fungicidal activity (Tillmann, Gow and Brown, 2011; Wagener et al ., 2017; Navarathna, Lionakis and Roberts, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…TLR1, TLR2, and TLR6 were regarded as critical mediators for fungal colonization and inflammatory responses in the candidemia kidney. As expression of these TLRs in the kidney could be enhanced by deficiency of nitric oxide synthase 3, NOS inhibition might mitigate candidemia [44].…”
Section: Infectious Kidneymentioning
confidence: 99%